2016
DOI: 10.1007/s11356-016-7709-7
|View full text |Cite
|
Sign up to set email alerts
|

Microbial structure and nitrogen compound conversions in aerobic granular sludge reactors with non-aeration phases and acetate pulse feeding

Abstract: A technological system was developed for efficient nitrogen removal from real digester supernatant in a single reactor with shortened aeration to increase the economical aspects of wastewater treatment. The supernatant (600 mg TKN/L, low COD/N ratio of 2.2) was treated in batch reactors with aerobic granules (GSBRs) to test how one, two, or three non-aeration phases and acetate pulse feeding in the cycle affect the morphological and microbial properties of biomass. Introduction of one non-aeration phase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 51 publications
0
3
1
Order By: Relevance
“…This indicates that ammonium nitrogen oxidation is stimulated by anoxic conditions. It has been reported that increasing the number of anaerobic phases in the reactor cycle increased the total number of bacteria (as shown by abundance of 16S rRNA gene), the number of AOB bacteria involved in nitrification (amoA gene abundance) and the number of complete denitrifiers (nosZ gene abundance) [34]. In the present study, such increases were not observed; however, the share of such taxa as Thauera sp., Dokdonella ginsengisoli, and Lysobacter daejeonensis, which participate in nitrogen The average N-NH 4 concentration in each effluent was around 1 mg L −1 (Figure 4).…”
Section: Resultscontrasting
confidence: 64%
See 1 more Smart Citation
“…This indicates that ammonium nitrogen oxidation is stimulated by anoxic conditions. It has been reported that increasing the number of anaerobic phases in the reactor cycle increased the total number of bacteria (as shown by abundance of 16S rRNA gene), the number of AOB bacteria involved in nitrification (amoA gene abundance) and the number of complete denitrifiers (nosZ gene abundance) [34]. In the present study, such increases were not observed; however, the share of such taxa as Thauera sp., Dokdonella ginsengisoli, and Lysobacter daejeonensis, which participate in nitrogen The average N-NH 4 concentration in each effluent was around 1 mg L −1 (Figure 4).…”
Section: Resultscontrasting
confidence: 64%
“…This indicates that ammonium nitrogen oxidation is stimulated by anoxic conditions. It has been reported that increasing the number of anaerobic phases in the reactor cycle increased the total number of bacteria (as shown by abundance of 16S rRNA gene), the number of AOB bacteria involved in nitrification (amoA gene abundance) and the number of complete denitrifiers (nosZ gene abundance) [34].…”
Section: Resultsmentioning
confidence: 99%
“…The increase in residual nitrate (Fig 3b , phase-A) in treated effluent at start-up period could be from seed municipal wastewater as the nitrification pathway was limited due to low bacteria population. The steady reduction in nitrate which ensued at limited nitrification phase implies denitrification of the near constant residual (original) nitrate believed to have occurred within the anaerobic environment of aerobic granules and flocs created due to limited air diffusion in the biomass structure [34,35,36]. The sudden increase in nitrate concentration in treated effluent from day 28 was in tandem with the nitrification activity shown in Figure 3a, phase-A.…”
Section: Removal Of Nutrientsmentioning
confidence: 90%
“…Similarly, seed municipal wastewater was responsible for the sudden decrease in phosphate concentration in treated effluent which gradually increased in response to increased feed dosage (Fig 3c , phase-A). The subsequent gradual reduction in phosphate in the aerated bioreactors could be by denitrifying phosphate accumulating organisms process [34,42,43].…”
Section: Removal Of Nutrientsmentioning
confidence: 99%